Plan de exportación de aguacate Hass colombiano a Países Bajos (2025)
The Hass avocado export program aims to position itself in international markets through a strategy based on operational efficiency and sustainability. This plan includes a robust initial investment, based on financial analyses that project a recovery between the first and second year, due to the positive relationship between costs and income. Market analyses indicate a high global demand for Hass avocado, highlighting its acceptance for its quality and versatility. This product is aimed at the international market, where healthy consumption is a growing trend.